Pulsed focused ultrasound ablation assisted by a surface modified catheter for thrombolysis: a feasibility study - Samaddar, Abhirup; Forrest, M. Laird; Yang, Xinmai (Frontiers in Acoustics, 2024)
Interventional procedures for the recanalization of blood vessels to treat deep vein thrombosis carry a high risk of vessel wall injuries or hemorrhaging. Focused ultrasound (FUS) has been used to non-invasively break down blood clots that occlude the vessels in both in vitro and in vivo studies. Previous studies have either used thrombolytic drugs or ultrasound contrast agents (e.g., microbubbles) in combination with FUS. Several studies have applied very high peak-negativepressures (PNP) during FUS treatment to achieve successful thrombolysis without the use of contrast agents. In the current study, we demonstrated that cavitation activity could be significantly enhanced by placing a nitinol wire, whose surface was roughed by laser etching, in the focal region of a FUS field. We demonstrated in vitro in a mock thrombosis that the thrombolysis efficacy of a 500 kHz FUS transducer was significantly enhanced using a surface-etched nitinol wire as compared to an unetched nitinol wire, whereas FUS-alone at the same pressure level did not result in any thrombolysis. These results suggest that a surface modified nitinol catheter exposed to FUS can result in intense cavitation activities leading to enhanced thrombolysis without the use of additional pharmacological or contrast agents.